Improvement of embryo production by the replacement of the last two doses of porcine follicle-stimulating hormone with equine chorionic gonadotropin in Sindhi donors - Mattos, M. C. C. [UNESP]; Bastos, M. R. [UNESP]; Guardieiro, M. M.; Carvalho, J. O.; Franco, M. M.; Mourao, G. B.; Barros, C. M. [UNESP]; Sartori, R. (Elsevier B.V., 2011)
The aim of this study was to evaluate the superovulatory (SOV) response of Sindhi (Bos indicus) donors submitted to an ovarian follicular superstimulatory protocol replacing the last two doses of pFSH by eCG. Forty-eight SOV treatments were performed in a crossover design in 19 nulliparous and primiparous females that were randomly divided into two groups: FSH (n=24), which consisted of eight pFSH injections, or FSH/eCG (n=24), which consisted of six pFSH injections followed by two eCG injections. Each female underwent two or three SOV treatments that consisted of an i.m. injection of 2 mg estradiol benzoate and the insertion of an intravaginal progesterone-releasing device on Day 0, on Day 4, superstimulatory treatments were initiated and 100 mg pFSH was divided into twice daily decreasing doses over a 4-day period. In the FSH/eCG group, the last two doses of pFSH were replaced by two doses of eCG (150 IU eCG each). At the time of the fifth and sixth injections of FSH, 0.150 mg PGF(2 alpha), was injected i.m. The intravaginal progesterone-releasing device was removed at the time of the last FSH or eCG injection and ovulation was induced with 0.2 mg GnRH 18 h later. All females were artificially inseminated with frozen-thawed semen from the same bull 6 and 18 h after GnRH treatment. Seven days after GnRH treatment, embryos/ova were recovered and classified. Follicular superstimulatory (number of follicles >= 6 mm at the time of the last FSH or eCG injection) and SOV (CL number) responses were determined by transrectal ultrasonography. Data were analyzed using generalized linear models and results were presented as least squares means +/- standard error. The FSH/eCG group had higher superstimulatory (33.8 +/- 3.9 compared to 23.8 +/- 2.6 follicles; P=0.03) and SOV (16.8 +/- 2.9 compared to 10.8 +/- 2.1 CL; P=0.10) responses. Although the number of total ova/embryos was not different between groups (8.2 +/- 1.8 compared to 5.9 +/- 1.4 for FSH/eCG and FSH groups, respectively; P=0.25), the number (5.8 +/- 1.3 compared to 2.6 +/- 0.7; P=0.02) and percentage (75.6 +/- 5.7 compared to 53.2 +/- 9.7%; P=0.05) of transferable embryos was greater for the FSH/eCG females. Therefore, there was improvement in follicular superstimulatory and SOV responses and embryo quality in FSH/eCG-treated females. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ovarian follicle superovulation; eCG; Embryo; Bos indicus